Perception Regarding Care of Attempted Suicide Patients among Nursing Students in Kathmandu University School of Medical Sciences - Bajracharya, J.; Bhandari, N.; Chalise, P.; Tiwari, D. (Kathmandu University Medical Journal, 2020)
Background Suicide is an act of deliberately killing oneself. It is a global health problem and is the second leading cause of death in 15 to 29 years. Thus, studying nursing students’ perception towards suicide attempters has paramount importance in understanding and addressing the existing gaps in healthcare delivery system. Objective To assess the nursing students’ perception towards attempted suicide and to find out the association between perception and selected variables. Method A descriptive, cross sectional design was carried out to assess the nursing students’ perception towards suicide attempters in Kathmandu University School of Medical Sciences. The respondents were 193 nursing students. A structured questionnaire was used in order to collect data. Descriptive statistics including frequency, percentage, mean and standard deviation were calculated to summarize the data and inferential statistics, Mann Whitney-U test was used for the association between perception and selected variables. Result A total 193 nursing students participated in this study. The scores between 1 and 2.4 were considered ‘positive’, ‘unsure’ or ‘uncertain’, between 2.5 and 3.4 and negative for 3.5 and above’ over all nurses showed relatively negative perception towards suicide attempters. According to results from eight domains of perception, those who did not attend the courses on psychiatry nursing presented higher score, which was found to have significant association with permissiveness, unpredictability and incomprehensibility. A younger nursing student shows significant association with incomprehensibility. Younger nursing student showed statistically significant association with duration of suicide process. Conclusion Nursing students are frequently encountered with attempted suicide patients. Therefore, they must be aware of their attitudes toward this group of patients as part of their professional and therapeutic role. Thus a nurse’s positive perception towards attempted suicide can play a key role in communicating and preventing a future suicide attempt.